2019
DOI: 10.1007/s00464-019-07239-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgical flow disruptions on surgeons’ resources: a pilot study

Abstract: Important note To cite this publication, please use the final published version (if applicable). Please check the document version above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…First, some consequences of frequent FDs on performance cannot be detected by our study design: this includes long-term effects of FDs on surgeon’s decision making, mental resources, and fatigue, as well as accumulated effects of consecutive FDs (i.e. FD cascades) [ 12 , 54 ]. It has been suspected that only severe or accumulated FDs may have a negative effect on surgical performance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, some consequences of frequent FDs on performance cannot be detected by our study design: this includes long-term effects of FDs on surgeon’s decision making, mental resources, and fatigue, as well as accumulated effects of consecutive FDs (i.e. FD cascades) [ 12 , 54 ]. It has been suspected that only severe or accumulated FDs may have a negative effect on surgical performance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Van Houwelingen et al showed that experts in laparoscopic procedures exhibit fewer physical reactions than novices to disturbances during surgery. [ 22 ]. Moorthy et al tested 12 surgeons with different levels of expertise (4 experts and 8 novices) on a laparoscopic trainer, using three levels of noise: quiet, 80–85 dB, and music.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have demonstrated the negative impact of disruptive factors on the surgical performance of students and surgical novices practicing on a virtual reality trainer [ 5 ]. Experienced surgeons performing conventional surgery have been tested for the impact of disruptive factors [ 9 , 20 , 21 , 22 ]. However, data concerning the impact of distractions on surgical performance among experienced surgeons performing minimally invasive surgery are scarce [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations